Representation of lung cancer in online Malaysian newspapers. - Ting, Su Hie; Jonnie Kiew, Heng Beng (Asian Scholars Network (ASNet), 2023)
The study examined the representation of lung cancer in online Malaysian newspapers published in English. The objectives were to: (1) compare the frequency of information on severity, susceptibility, recommended actions, benefits and barriers in the newspapers; and (2) describe themes and sub-themes of these Health Belief Model constructs. The 12 online newspaper articles (2 New Strait Times, 4 The Star, 1 The Borneo Post and 5 The Sun) were analysed using the Health Belief Model. There were 89 instances of information on lung cancer. The newspaper articles crafted the threat of lung cancer through emphasis on severity (25.84%) and susceptibility (23.60%), particularly death statistics and tobacco smoking as a risk factor. The articles also recommended the public to take health protective actions (19.10%), and dealt with benefits (16.85%) and barriers (14.61%) to adoption of these behaviours. A chi-square test of independence showed significant differences among the newspapers on the frequency of information on severity, susceptibility, recommended actions, benefits, and barriers. However, the newspaper articles were similar in the highlight on the key benefits which were reducing deaths, improved health, and good treatment outcomes, and barriers which were inadequate knowledge and addiction. Half of the recommended actions to counter lung cancer were about the proposed tobacco ban for those born after 2005, and the rest were policy implementation issues, lifestyle changes and self-education. The study suggests that there is need for diversity of information on lung cancer in the media for better public health education.